Solving Job Shop Scheduling Problem Based on Employee Availability Constraint - Chandrasekaran, M.; Ramya, G. (Applied Mechanics and Materials, 2013)
Manufacturing System is enabled with an excellent knowledge on production plan, proper scheduling of machinery process, employee timetabling and labor costs. Heuristic algorithms are developed to bring optimized results in stipulated time with respect to optimum schedule. This article deals with minimizing the maximum completion time (makespan) based on job scheduling and minimization of labor costs based on employee workload with Shuffled Frog Leaping Algorithm and Sheep Flock Heredity Model Algorithm. The labor costs minimization and makespan which is to find a schedule that satisfies the organizations rules, employees preferences, due date and customers. The formulation of assigning workload for employees is concerned with assigning number of employees into a given set of shifts over a fixed period of time and week task. The main problem attempts to minimize labor costs based on performance criteria and assigning the loads equally among all employees. Several local search methods and heuristics algorithms has been proposed in many research on Job shop scheduling. The Results are compared with other heuristics in terms of makespan, idle time and Labor costs the Shuffled Frog Leaping algorithm performs result oriented than other Heuristics Algorithm.